Implementation of the student facilitator and explaining model assisted by media game on the students’ explaining skills - Prathini Khafifah Handayani; Asep Ginanjar Arip; Sofyan Hasanuddin Nur (University of Muhammadiyah Malang, 2022)
The students' explaining skill is interrelated with their conceptual understanding. This study aimed to determine the effect of the implementation of the student facilitator and explaining model assisted by the media game on the students' explaining skills related to environmental pollution. This quasi-experimental research was using a pre-test post-test control group design. The population was 120 seventh graders of state junior high schools in West Java, Indonesia. The simple random sampling technique has resulted in two groups (control and experiment) samples, consisting of 32 students for each group. The data were analyzed using the paired sample t-test. This study found that the student facilitator and explaining model assisted by the media game can significantly improve students' explaining skills (p-value 0.001 < 0.05). The students in the experimental group had a better understanding of the concept of environmental pollution. This study concludes that the student facilitator and explaining model assisted by the media games can improve students' explaining skills and understanding of environmental pollution.